2021
DOI: 10.3390/nu13103374
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Based Dietary Patterns and Breast Cancer Recurrence and Survival in the Pathways Study

Abstract: Plant-based diets are recommended for cancer survivors, but their relationship with breast cancer outcomes has not been examined. We evaluated whether long-term concordance with plant-based diets reduced the risk of recurrence and mortality among a prospective cohort of 3646 women diagnosed with breast cancer from 2005 to 2013. Participants completed food frequency questionnaires at diagnosis and 6-, 25-, and 72-month follow-up, from which we derived plant-based diet indices, including overall (PDI), healthful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Dietary patterns shown to reduce mortality and improve overall survival among patients with BC include a low-fat diet (13, [69][70][71][72], diabetes risk-reduction diet (14), plant-based diet (73), and anti-inflammatory diet (74). However, different studies have shown different results in terms of all-cause mortality, specific mortality, total mortality, cancer recurrence, and non-BC-related deaths among BC patients, indicating the need for more research.…”
Section: Dietary Patterns and Prognosis Of Bcmentioning
confidence: 99%
“…Dietary patterns shown to reduce mortality and improve overall survival among patients with BC include a low-fat diet (13, [69][70][71][72], diabetes risk-reduction diet (14), plant-based diet (73), and anti-inflammatory diet (74). However, different studies have shown different results in terms of all-cause mortality, specific mortality, total mortality, cancer recurrence, and non-BC-related deaths among BC patients, indicating the need for more research.…”
Section: Dietary Patterns and Prognosis Of Bcmentioning
confidence: 99%
“…Tables S6 and S7 show the characteristics and main results of the studies identified investigating data driven or predefined dietary and lifestyle patterns 6,34‐56 …”
Section: Resultsmentioning
confidence: 99%
“…The figure should not be interpreted as a quantitative summary. The Pathways study which reported the point estimate per each 10‐point increase of plant‐based dietary index (total, healthy and unhealthy; Anyene 2021) 49 was not included in the figure. Results from Wang 2020 44 and Wu 2020 48 for breast cancer‐specific mortality, and from Wu 2020 56 for recurrence were not included because competing risk regression models were employed.…”
Section: Resultsmentioning
confidence: 99%
“…The prementioned co-benefits for human and environment health can be achieved by adhering to diets that consider both nutritional quality and planetary health [7]. It is however important to find a way of distinguishing between healthy and unhealthy plant-based diets in order to achieve a healthful dietary pattern [8]. The dietary pattern index could be a useful tool for determining dietary quality [9].…”
Section: Knowledge Transfer Of Bruno Abreu (Porto) and Nicole Erickso...mentioning
confidence: 99%